Alpinia zerumbet Extract Mitigates PCB 126-Induced Neurotoxicity and Locomotor Impairment in Adult Male Mice - Paula Hosana Fernandes da Silva; Jemima Isnardo Fernandes; Matheus Pontes de Menezes; Fabrícia Lima Fontes-Dantas; André Luiz Nunes Freitas; Rayane Efraim Correa; Ulisses Cesar de Araujo; Dayane Teixeira Ognibene; Cristiane Aguiar da Costa; Cláudio Carneiro Filgueiras; Alex Christian Manhães; Júlio Beltrame Daleprane; et al. (Scientia Pharmaceutica)
Polychlorinated biphenyls (PCBs) are synthetic chemical compounds that have bioaccumulated and contaminated the entire global ecosystem, causing neurotoxic effects. However, polyphenols may have protective effects against this neurotoxicity. We aimed to investigate the neuroprotective effect of a hydroalcoholic extract of fresh leaves of Alpinia zerumbet (ALE), which is rich in polyphenols, on the neurobehavioral changes induced by 3,3′,4,4′,5-pentachlorobiphenyl (PCB 126). We divided C57BL/6 male mice into four groups (n = 40): Control, Control + ALE, PCB, and PCB + ALE. We administered the ALE (50 mg/kg/day) through drinking water and PCB 126 (2 mg/kg/once a week) intraperitoneally for four weeks. The mice were subjected to the elevated plus maze (EPM) and open field (OF) tests in the last week of treatment. PCB 126 reduced locomotor activity, DOPAC levels, dopamine turnover, and D2 receptor expression. This compound also increased lipid peroxidation, tyrosine levels, and BAX expression in the cerebral cortex. Notably, ALE treatment prevented locomotor activity reduction and increased DOPAC levels, dopamine turnover, and D2 receptor expression. Moreover, the extract prevented the PCB-induced increases in BAX expression and lipid peroxidation. Finally, the ALE increased SOD antioxidant activity. Our investigation highlights that using the ALE may serve as a therapeutic strategy against PCB-induced neurotoxicity.